Analisis Efektivitas Penerapan Tax Amnesty di Indonesia - Dimas Arif, Muhammad; Abdillah Siregar, Asyhari; Sipahutar, Sandi (Baashima : Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2024)
The implementation of the tax amnesty policy in Indonesia is the government's effort to increase tax revenues, reduce tax avoidance, and encourage tax compliance. This research aims to analyze the effectiveness of implementing tax amnesty in Indonesia by looking at its impact on tax revenue, tax avoidance, and tax compliance. In this research, researchers conducted research using qualitative descriptive methods. This research is an investigation of secondary data obtained through library research, such as articles, books, and sources related to research. The data analysis techniques used by researchers are data collection, data reduction, data presentation, data analysis, checking data validity, and drawing conclusions. The results of this research show that the effectiveness of amnesty requests to increase tax revenue have not been effective, as shown by figures below 10%, while amnesty requests to increase tax revenue have not reached Rp. 135,000,000,000,000 (did not meet target). The effect of implementing the tax amnesty on increasing the number of taxpayers is taken into account in the effective rate, namely due to an increase in the number of taxpayers. The effectiveness of the implementation of tax amnesty at the level of taxpayer compliance with tax declarations has not been effective, because the objectives and results of compliance with tax declarations have not been achieved.